Changes in macroalgal palatability and herbivore's behavior under ocean warming scenarios: consequences for top-down control - Ferreira, Ana Paula; Chow, Fungyi; Machado, Glauco B O [UNESP]; Leite, Fosca P P (Elsevier, 2025)
Ocean warming is a major driver of change in marine ecosystems, affecting organisms and their ecological interactions. Herbivory, a key ecological interaction, can be influenced by temperature. Understanding how climate change affects these interactions requires assessing temperature effects on both interacting species. The aim of this study was to investigate the direct and indirect effects of ocean warming on the chemical composition of the brown macroalga Sargassum filipendula and the feeding behavior of herbivorous amphipods. Specifically, we asked: (1) How does increased seawater temperature affect the nutritional value and defense compounds of S. filipendula? (2) How does ocean warming affect the feeding behavior of amphipods both directly and indirectly (via changes in macroalgae)? We conducted mesocosm experiments in which macroalgae were grown at 25 °C and 30 °C and amphipods were fed at the same temperatures in an orthogonal design. Warming altered the C/N ratio and the concentrations of carbon, carbohydrates, and phenolic compounds, but not protein and nitrogen, of S. filipendula tissues. The herbivorous amphipod Sunamphitoe pelagica responded directly to temperature, increasing its consumption at higher amphipod temperatures but decreasing it when macroalgae were grown at 30 °C. In contrast, the herbivorous amphipod Cymadusa filosa only reduced feeding when both amphipods and macroalgae were exposed to 30 °C. Nutrient quality appeared to be more important than defense compounds for consumption rates. Our results highlight the complexity of warming effects on trophic interactions and the importance of assessing direct and indirect temperature effects together.